Answers

2014-07-31T20:56:06+05:30
Here we use
Sn = (n/2)(2a+(n-1)d) 
90 = (n/2)(4+(n-1)8) 
180 = n(8n-4) 
180 = 8n^2-4n 
8n^2-4n-180 = 0 
n=5 
4 4 4
2014-07-31T21:11:36+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
An = a + d (n -1 )
Sn = n * [ a  +  a + d (n-1) ]  / 2  =  n * mean of 1st term and nth term
90 =  n * [ 4 + 8 n - 8 ] /2 =>  180 = 8 n² - 4 n    =>  2 n² - n - 45 = 0
n = 5    => An = 2 + 4 * 8 = 34

0